Regulation of electron transport is essential for photosystem I stability and plant growth. Issue 4 (18th June 2020) - Storti, Mattia; Segalla, Anna; Mellon, Marco; Alboresi, Alessandro; Morosinotto, Tomas
Summary: Photosynthetic electron transport is regulated by cyclic and pseudocyclic electron flow (CEF and PCEF) to maintain the balance between light availability and metabolic demands. CEF transfers electrons from photosystem I to the plastoquinone pool with two mechanisms, dependent either on PGR5/PGRL1 or on the type I NADH dehydrogenase‐like (NDH) complex. PCEF uses electrons from photosystem I to reduce oxygen and in many groups of photosynthetic organisms, but remarkably not in angiosperms, it is catalyzed by flavodiiron proteins (FLVs). In this study, Physcomitrella patens plants depleted in PGRL1, NDH and FLVs in different combinations were generated and characterized, showing that all these mechanisms are active in this moss. Surprisingly, in contrast to flowering plants, Physcomitrella patens can cope with the simultaneous inactivation of PGR5‐ and NDH‐dependent CEF but, when FLVs are also depleted, plants show strong growth reduction and photosynthetic activity is drastically reduced. The results demonstrate that mechanisms for modulation of photosynthetic electron transport have large functional overlap but are together indispensable to protect photosystem I from damage and they are an essential component for photosynthesis in any light regime. Abstract : See also the Commentary on this article by Leister, 228 : 1166–1168 .